Structure-Inspired Lineage-Specific Matrix for Endogenous Neurogenesis in Spinal Cord Injury - Bo Wu; Xuejiao Lei; Xufang Ru; Jiangling Zhou; Hao Liu; Yibo Gan; Yan Wang; Wenyan Li (Research)
Spinal cord injury (SCI) poses substantial challenges, often leading to permanent disability and requiring adequate neuronal regeneration for functional repair. Decellularized spinal cord (DSC) matrices hold promise due to their native 3-dimensional (3D) structure and extracellular matrix (ECM)-derived biochemical components. However, their limited mechanical properties and insufficient availability of growth factors hinder their effectiveness. To address these limitations, this study introduces a core–shell design that reinforces DSC with a hydrogel-based matrix capable of delivering essential growth factors while preserving its natural structure. By leveraging 3D printing and electrostatic adsorption, the engineered matrix retains the topological features of DSC while introducing new topographical and neurogenic cues. These instructive cues facilitated an 11-fold increase in the number of newly generated neuronal cells, demonstrating lineage-specific neuronal regeneration in vivo. Mechanistically, the synergistic effects of ECM-inspired structure and biochemical cues activated the ITGA2/ITGA11–ERK/AKT signaling axis and promoted M2 macrophage/microglia polarization, thereby reducing cavity and scar formation. This optimized microenvironment enhanced endogenous neurogenesis and supported functional recovery after SCI. Overall, this study developed a structure-inspired lineage-specific matrix that effectively stimulates endogenous neuronal regeneration, highlighting its potential for advancing spinal cord repair strategies.